Is God a Substance? Avicenna on Essence, Being, and the Categories - Taylor, Nathaniel B. (Religions, 2023)
Avicenna scholars unanimously agree that Avicenna takes the position that God is not classifiable according to the Aristotelian scheme of the ten categories. However, Avicenna scholars are in little agreement about precisely why God evades categorial classification. Scholars report numerous and, at times, mutually inconsistent arguments purportedly made by Avicenna. In this study, I argue that Avicenna has only one argument as to why God is not in the category of substance—the Essence-Being Distinction Argument—and that he makes this argument consistently throughout his major philosophical encyclopediae. Having clarified this argument, two consequences follow. First, we can study this argument to learn not only about God in Avicenna’s philosophical theology but also about the nature and structure of the categories in Avicenna’s metaphysics. I argue that Avicenna’s Essence-Being Distinction Argument reveals a route by which one may arrive at a real distinction between essence and being from a philosophical, rather than a theological premise. Second, Avicenna’s Essence-Being Distinction Argument, along with the prevalence and consistency thereof, suggests that God has an essence for Avicenna and that texts, wherein Avicenna denies that God has an essence, are exceptional and should not govern our broader interpretation of Avicenna’s philosophical theology.